2015
DOI: 10.1007/s12035-015-9142-1
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between Exosomes, microRNAs and Toll-Like Receptors in Brain Disorders

Abstract: Extracellular vesicles (EVs), including exosomes, microvesicles and apoptotic bodies, participate in intercellular communication, and particularly, in paracrine and endocrine signalling. The EVs and their specific contents have been considered hallmarks of different diseases. It has been recently discovered that EVs can co-transport nucleic acids such as DNAs, ribosomal RNAs, circular RNAs (circRNAs), long noncoding RNAs (lnRNAs) and microRNAs (miRNAs). miRNAs are important regulators of gene expression at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 180 publications
1
61
0
Order By: Relevance
“…Recent studies have demonstrated the usefulness of this novel biomarker technology for prognosis as well as biological mechanisms for AD in the general population (Paschon et al 2016; Rajendran et al 2006; Riancho et al 2017; Sharples et al 2008; Vingtdeux et al 2012; Xiao et al 2017; Yuyama and Igarashi 2017), and can also be used for studying the propagation of pathology within the brain (Polanco et al 2016; Winston et al 2016). We are hopeful that this novel methodology can shed light on early events in the pathology in DS-AD and hopefully lead to novel intervention or prevention therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated the usefulness of this novel biomarker technology for prognosis as well as biological mechanisms for AD in the general population (Paschon et al 2016; Rajendran et al 2006; Riancho et al 2017; Sharples et al 2008; Vingtdeux et al 2012; Xiao et al 2017; Yuyama and Igarashi 2017), and can also be used for studying the propagation of pathology within the brain (Polanco et al 2016; Winston et al 2016). We are hopeful that this novel methodology can shed light on early events in the pathology in DS-AD and hopefully lead to novel intervention or prevention therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes participate in intercellular communication in the brain. A recent study showed that neuro-derived exosomes carrying specific types of miRNAs can activate Toll-like receptors (TLRs) and thus trigger inflammation signaling in the brain either in neighboring cells or during long-distance cell-to-cell communication via exosome transport in the extracellular matrix (Paschon et al 2016). Studies have also shown that activation of microglia, for example by the presence of amyloid, increases the release of exosomes, which may then directly participate in the inflammatory process in the brain (Hooper et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…MVs carry and may shuttle specific proteins and noncoding nucleic acids such as microRNAs [200]. In fact, some miRNA may be found in MVs at higher concentrations than in cells [201]. For these reasons, besides their potential as disease biomarkers [202], MVs and exosomes are considered to have a role in the pathogenesis and dissemination of inflammatory diseases.…”
Section: Microglia May Drive Als Pathophysiologymentioning
confidence: 99%
“…However, if an asRNA is the target, this may instead result in the elimination of a blockade. In addition to interactions with other RNAs, some miRNAs have been shown to also target specific toll-like receptors (TLRs) [9][10][11]. However, this is only possible with TLRs that are capable of binding single-stranded RNAs (ssRNAs) but not double-stranded RNAs (dsRNAs).…”
Section: Introductionmentioning
confidence: 99%